2001
DOI: 10.1089/107555301750463215
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Medicine Teaching at the Universities of the European Union

Abstract: Unconventional medicine courses are widely represented at European universities. They cover a wide range of therapies. Many of them are used clinically. Research work is underway at several faculties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 18 publications
3
20
0
3
Order By: Relevance
“…7,8 In Europe, CAM-related courses are a part of the regular curriculum in 40% of medical departments and 72% of health sciences departments, respectively. 9,10 However, most CAM courses are elective and mostly focused on only 1 CAM therapy. 8 In the Czech Republic, there are 2 pharmacy schools, both of which currently offer elective courses on homeopathy and herbal remedies to pharmacy students.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In Europe, CAM-related courses are a part of the regular curriculum in 40% of medical departments and 72% of health sciences departments, respectively. 9,10 However, most CAM courses are elective and mostly focused on only 1 CAM therapy. 8 In the Czech Republic, there are 2 pharmacy schools, both of which currently offer elective courses on homeopathy and herbal remedies to pharmacy students.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, 40% of the European Union's medical schools offered CAM Disciplines (13) . In the period between 1997-1998, research in 117 American medical schools (14) showed that 64% of them included CAM disciplines with an increase of this estimate in the latter surveys (15) .…”
Section: Discussionmentioning
confidence: 99%
“…In de Europese Unie wordt op ruim een derde van de onderzochte medische faculteiten onderwijs gegeven over complementaire behandelwijzen. [19][20] De doelen die men stelt bij het aanbieden van onderwijs over complementaire behandelwijzen in het buitenland komen redelijk overeen. Zowel in Noord-Amerika als in Europa is het kennismaken met complementaire behandelwijzen het meest genoemde doel.…”
Section: Medische Faculteiten In Het Buitenlandunclassified
“…[16][17] In Europa is het aantal faculteiten met complementaire behandelwijzen aanzienlijk lager. 19 …”
Section: Tabelunclassified